Faktor yang Mempengaruhi Keuntungan Usahatani Bawang Merah pada Kelompok Tani Sejati, Desa Songan B, Kecamatan Kintamani, Bali - RENATA, GIACINTA TYAS; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Factors Influencing Income of Red Onion on Kelompok Tani Sejati in Songan B Village, Kintamani District, Bali. Farmers expect greater production in order to optimize their expected income. Especially if the cultivated commodity is continue experiencing enhancement on its market’s demand along with the enhancement of the population such as red onion on Kelompok Tani Sejati. In order to increase income through the enhancement of the production, production factors and its costs determine the size of production obtained. This study aimed to analyze the influence of seeds, fertilizer costs, pesticide costs, labor wages, water costs and the size of the planting area that was conducted on Kelompok Tani Sejati in Songan Village, Kintamani District, Bali. The data were analyze using the profit analysis, multiple linear regression and statistic test with the help of SPSS. Based on the F test, the results showed that seeds, fertilizer costs, pesticide costs, labor wages, water costs and the size of the planting area silmutaneously affected the income. Based on the T test the results showed that seeds, pesticide costs and labor wages had significant effect on the income, while fertilizer costs, water costs and the size of the planting area had no significant effect on the income. Based on the result Kelompok Tani Sejati is expected to maximize the use of seeds as the input and to pay attention to the use of pesticide costs and labor wages in accordance with their functions so that the expense could be more effective.